Kayleigh Blanco: capstone - Blanco, Kayleigh, artist (Colorado State University. Libraries, 2014)
The artist's statement: In regards to the art world, I find it challenging to place myself into a category of style or idea because of how young I am as an artist. I am merely a tiny sprout that has planted itself among the oaks and redwoods of the art world. I can, however, find a pattern through each conquering I have made as I complete piece after piece. Patterns I find within my work today include bright color, photographic elements, clarity, realism, collage, motion, geometric shape, and interactivity. My personal logo is a trio of circles, each a different color. I find strength in solid colored shapes. The confidence that exudes in a simple, solid shape is matchless. The work of Ellsworth Kelly is a raw version of shapes exuding this confidence. My piece, "Latin Portraits" (2014), explores a repetitive arrangement of triangles that make up collages of celebrity faces. My renditions of photographic collage express my desire to be clear and realistic in my design work. Richard Hamilton's "Just What Is It That Makes Today's Homes So Different, So Appealing?" (1956), compliments my style and exploration in cut-out collage and photorealism. This can be seen in my work, "Sounds of Summer" (2013). My work takes a more literal route than abstract. In my piece, "Pepperchinita Website" (2013), I have arranged photographic elements to a page that give a realistic viewpoint of a chef working at a kitchen table. Within the piece, a photographed pestle provides a link to another webpage, allowing the website to be interactive and engaging. There is a wholeness in art that is repetitive, and consistent in that repetition. Bold blocks of color arranged together, imperialize an idea or design. Barnett Newman is a long-standing idol in my eyes of using color and shape to imperialize a piece. His long strips of paint were likely influential in my design, "Estes Park Logos" (2013). My exploration in repetition can be seen in the photographic design, "14th International Conference on X-Ray Lasers" (2014). In this piece, I have arranged opaque circles that surround and repeat the design of the dark-ringed laser device. The interlocking of the circles creates a solid core that draws a captivating, celestial shape. My obsession in the circular shape is repeated through many of my works including, "Pepperchinita Brochure" (2013), "Estes Park Summer CD" (2013), and again, my personal logo.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.